The relationship between leader-member exchange, perceived organizational support, and turnover intention: A study of the Portuguese navy - Temporão, Miguel (2020)
The purpose of the present study is to investigate the level of turnover intention in the employees (both military and civilian staff), of the Portuguese Navy in times of austerity measures such as salary reductions or loss of the holiday allowances which were imposed by Portuguese Government, the International Monetary Fund, European Commission, and the European Central Bank. Furthermore, we also wanted to test the relationship among turnover intention, leader-member exchange, and perceived organizational support. Data was collected through an online self-report questionnaire (N=122), targeting groups of employees in the Portuguese Navy such as in the different naval bases. The findings indicate that there is a relevant high level of turnover intention in the employees working for the Portuguese Navy. The results also confirm that leader-member exchange mediates the relationship between perceived organizational support and turnover intention. Lastly, management implications of the findings, limitations, and suggestions for future research are also discussed.